The Sustainability of Pancasila in Indonesian Education System - Ronald Maraden Silalahi; Untung Yuwono (Research in Social Sciences and Technology, 2018)
Pancasila as the ideological foundation of Indonesia is inseparable from education. In the implementation level, education is directed to build the values of Pancasila through learning programs. However, Indonesian education is still at an alarming condition, because the competencies of the graduates are not equivalent to the graduates from the other countries. This phenomenon underlies the formation of 2013 Curricula that emphasizes on the development of Pancasila values as the core competencies. This research was aimed at reconstructing Pancasila ideology and discussing the steps to revitalize Pancasila in Indonesian education system. Critical Discourse Analysis was conducted in three stages, namely text description, discursive practice, and socio-cultural practice to reconstruct Pancasila ideology in 2013 Curricula and their juridical foundations. Focus Group Discussions were conducted to review the application of the 2013 curriculum as well as the revitalization of Pancasila in Indonesian education system. The analysis revealed that the revitalization in Indonesian education system is absolutely needed, because the values of Pancasila as one of the core competencies that must be owned by the students have not been fundamentally and appropriately implemented in education and learning process.